High-intensity interval training versus moderate-intensity continuous training on exercise capacity and quality of life in patients with coronary artery disease: A systematic review and meta-analysis - Durães, André R. (2017)
Background: Exercise is an effective strategy for reducing total and cardiovascular mortality in patients with coronary artery disease. However, it is not clear which modality is best. We performed a meta-analysis to investigate the effects of high-intensity interval versus moderate-intensity continuous training of coronary artery disease patients. Methods: We searched MEDLINE, PEDro, LILACS, SciELO and the Cochrane Library (from the earliest date available to November 2016) for controlled trials that evaluated the effects of high-intensity interval versus moderate-intensity continuous training for coronary artery disease patients. Weighted mean differences and 95% confidence intervals were calculated, and heterogeneity was assessed using the I 2 test. Results: Twelve studies met the study criteria, including 609 patients. High-intensity interval training resulted in improvement in peak oxygen uptake weighted mean difference (1.3 ml/kg/min, 95% confidence interval: 0.6–1.9, n ¼ 594) compared with moderate-intensity continuous training. No significant difference in physical, emotional, and social domain of quality of life was found for participants for participants in the high-intensity interval training group compared with the moderate-intensity continuous training group. Sub-analysis of three studies with isocaloric exercise training showed no significant difference in peak oxygen uptake weighted mean difference (0.4 ml/kg/min, 95% confidence interval: –0.1–0.9, n ¼ 137) for participants in the high-intensity interval training group compared with moderate-intensity continuous training group. Conclusions: High-intensity interval training may improve peak oxygen uptake and should be considered as a component of care of coronary artery disease patients. However, this superiority disappeared when isocaloric protocol is compared.